HISTORY OF DEVELOPMENT OF THE DOMESTIC LEGAL REGULATION OF THE CONSTRUCTION CONTRACT FROM ANCIENT TIMES TO 1995 - MALIUSHEV A.V. (Legal Bulletin)
Due to the rapid growth of civil and industrial construction, there is a demand for adequate and understandable legal regulation of the relevant socio-economic relations. There is a need for sources to which the participants of contractual legal relations could refer in order to resolve disputable situations. It seems important to refer to the history of the development of regulation of the institute of construction contracting, as this will help to establish what place the institute occupies in the systematics of domestic civil law, the basic principles of its work and characteristic features. The main purpose of this paper is to analyze the development and changes of the institute of construction contract in the Russian